The Impact of Leadership Style, Compensation, and Work Environment on Employee Performance with Job Satisfaction as an Intervening Variable at Chanadia Resto - Nur Wahyu Setyaningrum; Sutrisno; Sumastuti, Efriyani (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The study at Chanadia Resto examined how leadership style, compensation, and work environment influence employee performance, with job satisfaction as a mediating factor. Using data from 104 employees, it found that both leadership style and work environment positively impact employee performance, while compensation does not have a significant direct effect. Job satisfaction mediates the effects of leadership style and work environment but not compensation. The findings suggest that fostering effective leadership and a positive work environment enhances employee performance through increased job satisfaction. Although compensation did not directly impact performance, it remains crucial for motivation and retention. Chanadia Resto management is encouraged to focus on leadership development, a supportive work environment, and job satisfaction to boost employee performance.